Consumer acceptance mobile banking di bank swasta indonesia - Herning Indriastuti (Faculty of Economics and Business Mulawarman University, 2020)
This research main investigates analyze factors such as perceived usefulness, perceived to use, perceived risk , compatibility to attitude and intention to use of mobile banking in Indonesia private banking. This reseach used quantitative approach with AMOS and used 195 samplings data with purposive sampling technique. Based on structural model, the results that perceived usefulness, perceived easy to use and compatibility to use have a positive and significant effect to attitude, perceived risk does not significant effect to attitude and compatibility does not significant effect to intention to use. Attitude has significant effect to intention to use mobile banking. Based on the result of this reseach, it is expected that private bank should maintain the value of usefulness as major factor in increasing user intention of using mobile banking.